20.8k views
5 votes
Rewrite the function f(x)=-2(x-3)^2+7 in the form f(x)=ax^2+bx+c

User Azmath
by
6.3k points

1 Answer

2 votes

Answer:

f(x) = -2x² + 12x - 11

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Expand by FOIL (First Outside Inside Last)
  • Standard Form: f(x) = ax² + bx + c
  • Vertex Form: f(x) = a(bx + c)² + d

Explanation:

Step 1: Define function

Vertex Form: f(x) = -2(x - 3)² + 7

Step 2: Find Standard Form

  1. Expand by FOILing: f(x) = -2(x² - 6x + 9) + 7
  2. Distribute -2: f(x) = -2x² + 12x - 18 + 7
  3. Combine like terms (constants): f(x) = -2x² + 12x - 11
User Krisragh MSFT
by
6.1k points